Anterior Ischemic Optic Neuropathy After Dental Extraction. Issue 1 (March 2019) - Kravitz, Elizabeth; Foroozan, Rod
Abstract : Background: While often idiopathic, anterior ischemic optic neuropathy occasionally may occur from an identifiable cause. Methods: Observational case report. Results: A 19-year-old woman with unremarkable medical and ophthalmic histories developed visual loss from nonarteritic anterior ischemic optic neuropathy in her right eye after otherwise uneventful dental extraction of the inferior third molars. Conclusions: Anterior ischemic optic neuropathy may rarely occur after dental extraction. Potential pathophysiologic mechanisms of this rare occurrence are discussed.